2019
DOI: 10.21203/rs.2.17372/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Professional oral care in end-of-life patients with advanced cancers in a hospice ward: Improvement of oral conditions

Abstract: Background: In end-of-life patients with advanced cancers, oral examination, oral care, and oral re-examination are crucial. Although oral symptoms are among the major complaints of end-of-life patients, few studies have focused on oral care in these patients. In this study, the association between oral symptoms and oral dryness among end-of-life patients was examined, and improvement of oral conditions after oral care interventions by a professional dentist was quantified. Methods: This prospective interventi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
1
1
0
4
Order By: Relevance
“…On the other hand, fungal amount was related with oral moisture condition and OHAT. Wu et al reported that oral care intervention in patients at the end stage of cancer reduced detection of Candida on the tongue, accompanied by a decrease in OHAT score [52], which was con rmed by the present results. OHAT criteria includes dryness in assessments for lip, tongue, gums and tissues, and saliva.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, fungal amount was related with oral moisture condition and OHAT. Wu et al reported that oral care intervention in patients at the end stage of cancer reduced detection of Candida on the tongue, accompanied by a decrease in OHAT score [52], which was con rmed by the present results. OHAT criteria includes dryness in assessments for lip, tongue, gums and tissues, and saliva.…”
Section: Discussionsupporting
confidence: 88%
“…Caso seja necessário, o dentista pode extrair dentes com mau prognóstico e restaurar aqueles com cárie, além de realizar raspagem e profilaxia para remover biofilme e cálculos, o que reduz o risco de infecções orais após a terapia (Mol, 2010). Segundo Wu et al (2020), a investigação e a intervenção do cirurgião-dentista em pacientes oncológicos em cuidados paliativos se faz essencial no controle e tratamento das condições relacionadas ao fluxo salivar. Da mesma forma, caso seja necessário, o profissional pode extrair os dentes com mau prognóstico e restaurar aqueles com cárie, além de realizar raspagem e profilaxia para remover biofilme e cálculos, o que reduz o risco de infecções orais após a terapia e melhora, por consequência, a saúde desse indivíduo (Mol, 2010).…”
Section: Wu Et Al (2020)unclassified
“…Como exposto por Wu et al (2020), a carência de informações propagadas ao paciente ou aos cuidadores sobre a correta higiene oral durante o tratamento, dificulta o estabelecimento da saúde dos tecidos dentais e periodontais. Dessa forma, a periodontite e a gengivite também estiveram associadas ao câncer (Venkatasalu et al, 2020;Amodio et al, 2014).…”
Section: Wu Et Al (2020)unclassified
See 2 more Smart Citations